Association between Dietary Glycaemic Index and Glycaemic Load and Adiposity Indices in Polycystic Ovary Syndrome - Melekoglu, Ebru; Goksuluk, Dincer; Yildiz, Emine Akal (Routledge Journals, Taylor & Francis Ltd, 2020)
Objective: Obesity is a key contributor to metabolic and reproductive outcomes in polycystic ovary syndrome (PCOS). The role of the dietary glycemic index (GI) and load (GL), and adiposity has been debated and studies on PCOS are scarce. We aimed to compare the dietary GI and GL and several anthropometric measurements in PCOS and control women. The association between dietary GI and GL and adiposity indices was examined in this cross-sectional study. Methods and materials: A study population consisted of 65 previously diagnosed with PCOS and 65 healthy women. All participants underwent detailed anthropometric, dietary and physical activity evaluation and categorized based on GI and GL tertiles. Results: When dietary GL was adjusted for age, physical activity level (PAL), and duration of diagnosis, there was a statistically significant inverse association between dietary GL and waist/hip ratio (WHR) (OR: 0.136; 95% CI: 0.021-0.874; p = 0.036) in women with PCOS. Both dietary GI (OR: 8.869; 95% CI: 1.194-65.910; p = 0.033 for tertile 2 in adjustment model) and GL (OR: 7.200; 95% CI: 1.635-31.712; p = 0.009 for tertile 3 in crude model; OR: 5.801; 95% CI: 1.242-27.096; p = 0.025 for tertile 3 in adjustment model) positively associated with WHR in healthy subjects. Also, positive association was observed between dietary GI and waist/height ratio (WHtR) (OR: 0.229; 95% CI: 0.063-0.826; p = 0.024 for tertile 2; OR: 0.277; 95% CI: 0.078-0.988; p = 0.048 for tertile 3) in healthy controls, however after adjustment for age and PAL, statistical significance was lost (OR: 1.051; 95% CI: 0.152-7.261; p = 0.959 for tertile 2; OR: 1.522; 95% CI: 0.225-10.297; p = 0.667 for tertile 3). Conclusion: The results of this study consistent with the literature that PCOS is associated with increased adiposity indices. There was no association between dietary GI/GL and BMI, WC, WHtR, and ABSI but dietary GL was inversely associated WHR in PCOS patients.
Keywords: Glycemic index; glycemic load; obesity; abdominal adiposity; polycystic ovary syndrome